Evaluating the Toxicity of Ionic Liquids on Shewanella sp. for Designing Sustainable Bioprocesses - Kebaili, Hakima; Pérez de los Ríos, Antonia; Salar-García, María José; Ortiz-Martínez, Víctor Manuel; Kameche, Mostefa; Hernández-Fernández, Jesús; Hernández-Fernández, Francisco J. (Frontiers in Materials, 2020)
Ionic liquids (ILs) are widely used as reaction and separation media in many technologies due to their unique and advantageous physicochemical properties. Thus, further studies approaching the study of the toxicity of these materials are required. Moreover, they are utilized in devices in which microorganisms such as Shewanella sp. act as biocatalysts. Thus, in this work, the toxicity of 69 ILs on the marine bacterium Shewanella sp. was tested. Specifically, the ILs analyzed were based on the cations imidazolium, pyridinium, pyrrolidinium, piperidinium, morpholinium, oxazolinium, phosphonium, ammonium, and sulfonium, in combination with different anions. The toxicities of this wide group of ILs on Shewanella sp. were determined using two methods: (i) the agar disk-diffusion test and (ii) the growth inhibition test in liquid media. The relationship between toxicity and IL chemical structure was elucidated. A decrease in the hydrophobicity of the alkyl chain length was found to be a key factor to reduce IL toxicity. On the other hand, phosphonium-based ILs containing long alkyl chains showed to be largely incompatible with Shewanella sp.